2010
DOI: 10.1249/mss.0b013e3181af21e2
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Pacing during Overground Hill Running

Abstract: Speed was best predicted using a weighted factor to account for prior and current gradients. Oxygen consumption (VO2) limited runner's speeds only on uphill sections and was maintained in line with individual ventilatory thresholds. Running speed showed larger individual variation on downhill sections, whereas speed on the level was systematically influenced by the preceding gradient. Runners who varied their pace more as a function of gradient showed a more consistent level of oxygen consumption. These result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
44
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 27 publications
7
44
0
2
Order By: Relevance
“…Considering all runners, stride rate was found to be greater at the 161.1 km site compared with the 90.3 km site but did not vary across sites among the top finishers. This is similar to previous studies in middle-distance runners that allowed a self-selected speed and demonstrated maintenance of stride rate despite a decrease in stride length over distance (6,36), and in endurance runners that demonstrated an increase in stride rate after completion of a mountain ultramarathon (28) or during a 24-hour treadmill run (26). Therefore, an increase in stride rate may represent an additional means by which runners can reduce impact forces.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Considering all runners, stride rate was found to be greater at the 161.1 km site compared with the 90.3 km site but did not vary across sites among the top finishers. This is similar to previous studies in middle-distance runners that allowed a self-selected speed and demonstrated maintenance of stride rate despite a decrease in stride length over distance (6,36), and in endurance runners that demonstrated an increase in stride rate after completion of a mountain ultramarathon (28) or during a 24-hour treadmill run (26). Therefore, an increase in stride rate may represent an additional means by which runners can reduce impact forces.…”
Section: Discussionsupporting
confidence: 88%
“…Stride length was significantly affected by finish place and site. The overall site effect (i.e., decreased stride length between 16.5 and 90.3 km) was similar to previous research in middledistance runners (6,36), marathon runners (12), and endurance runners (31). However, this change in stride length was not characteristic of the fastest runners.…”
Section: Discussionsupporting
confidence: 86%
“…Sloniger et al 16 observed a 9% higher muscle activation at a 10% inclination running, compared to flat running. This increased muscle activation is in line (a) with the greater relative contribution of the concentric force observed during uphill activity, (b) with a significantly higher metabolic cost, 17,18 and (c) with a pattern of differentiated muscular recruitment. 16 Positive chronotropic modifications and the heightened development of the slow component of oxygen consumption complete the list of significant physiological changes resulting from slope training.…”
supporting
confidence: 72%
“…The change in pace after 6.9 km occurred during level running, although this followed approximately 1.7 km of uphill and downhill running, and occurred in the presence of low and unchanged wind resistance and unchanged running surface. This would not appear to represent a readjustment to level running, since a short transient increase in speed is observed when level running is preceded by downhill running (Townshend et al 2010). When greater resolution was available (Fig.…”
Section: Discussionmentioning
confidence: 97%